Decoupling of industrial water consumption and economic expansion in the Yangtze River Economic Belt: a comparative analysis across three Five-Year plans - Xiujuan Gong; Shu Liu; Wei Ye; Liang Liu (Scientific Reports)
Abstract As the Yangtze River Economic Belt (YREB) continues its rapid economic expansion, the mismatch between the supply and demand of industrial water resources has become increasingly pronounced. While existing research has largely overlooked the decoupling dynamics between industrial water consumption and economic expansion in this region, this study provides a comprehensive analysis of its decoupling relationship, the stability, and the underlying driving forces. Drawing on data from 11 provinces and municipalities in the YREB spanning the 11th to 13th Five-Year Plan (FYP) periods, this study employs the Tapio decoupling model and the logarithmic mean divisia index (LMDI) model as its primary analytical tools. Through comparative analysis, the results reveal that the YREB’s overall decoupling status evolved from weak decoupling in the 11th FYP period to strong decoupling in the 12th and 13th periods, though marked regional disparities persist. Notably, all provinces exhibited some degree of decoupling reversal, primarily during plan transitions, the mid-term of the 12th FYP, or around 2019. This underscores the non-linear and dynamic nature of the decoupling process. In terms of driving factors, during the 11th and 12th FYP periods, the technological effect was the dominant force curbing industrial water consumption, while the output effect was the main contributor to its increase. The interplay between these opposing forces led to fluctuations in the total water consumption effect. However, by the 13th FYP period, structural effect emerged as a significant new restraining force. This study contributes empirical evidence and policy-oriented insights to improve sustainable industrial water management in major river basin economies.